Confronting the costs of war : military power, state, and society in Egypt and Israel - Barnett, Michael N., 1960- (Princeton University Press, 1992)
What determines the strategies by which a state mobilizes resources for war? And does war preparation strengthen or weaken the state in relation to society? In looking at these questions, Michael Barnett develops a novel theoretical framework that traces the connection between war preparation and changes in state-society relations, and applies that framework to Egypt from 1952 to 1977 and Israel from 1948 through 1977. Confronting the Costs of War addresses major issues in international relations, comparative politics, and Middle Eastern studies. The author argues that Egyptian and Israeli war preparation strategies were a function of systemic, state, and societal variables, and that leaders in each state attempted to balance the demands imposed by international conflict with their domestic economic and political objectives. Before 1967 the governments' strategies led to the expansion of state control over society. But contrary to the prevailing wisdom that war and war preparation will generally strengthen the state, the increased security pressures after 1967 were central to the decline of state power in both countries. After that year, Israeli and Egyptian officials ventured on a path that bolstered the state's military preparedness, but at the cost of its control over society and economy.